PENGARUH KESADARAN WAJIB PAJAK, SANKSI DENDA ADMINISTRASI PAJAK DAN PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PBB-P2 TAHUN 2016-2020 - Deska Fitri Amalia (Pascasarjana Universitas Sultan Ageng Tirtayas, 2022)
The Objective of the research is to analyze and review the examine analysis the effect of taxpayer awareness, tax administration fines and tax services on the tax payer compliance inpaying PBB-P2 for 2016-2020 years. The reseacrh method was used the descriptive andquantitative method. The population of data is the number all tax payer in PBB-P2 andsamples is 240 respondent. The analysis method used regression linier method. Based on theresearch partially result among the tax payer awareness is significant to the tax payercompliance,tax administration fines is significant on the tax payer compliance, the tax payerawareness is significant on the tax payer compliance, and tax services is significant on thetax payer compliance.The simultant result tax administration fines, the tax payer awarenessand tax services together was significant on the tax payer compliance.